THE INFLUENCE OF PROMOTION AND PRODUCT QUALITY ON PURCHASE DECISIONS FOR ERAFONE ACCESSORIES IN TANGERANG CITY - Sinta Sulistiani; Ratih Andalusi; Retno Wulansari (International Journal Management and Economic, 2025)
This study aims to analyze the influence of promotion and product quality on purchasing decisions for Erafon accessories at Hezal Cellular in Tangerang City. Using a quantitative approach, the research involved 125 respondents selected through probability sampling. Promotion was evaluated through advertising, sales promotion, and direct selling, while product quality was assessed based on performance, reliability, durability, and perceived quality. Purchasing decisions were measured by product choice, brand preference, purchase timing, and purchase quantity. The findings indicate that promotion has a positive and significant impact on purchasing decisions. Product quality also shows a significant positive influence. Combined, promotion and product quality explain 83.8% of the variance in purchasing decisions, highlighting their critical role in consumer behavior. This research concludes that enhancing promotional efforts and ensuring high product quality can significantly improve purchasing decisions. Hezal Cellular is advised to intensify targeted promotional activities and continuously improve product quality to meet consumer expectations and remain competitive in the market.